Food Insecurity across the Rural-Urban Divide: Are Counties in Need Being Reached by Charitable Food Assistance?. Issue 1 (July 2017) - Gundersen, Craig; Dewey, Adam; Hake, Monica; Engelhard, Emily; Crumbaugh, Amy S.
An extensive literature has described U.S. food insecurity and its determinants, but there has been little work on the geographic distribution of food insecurity and no work on the distribution of private food assistance by geography. To study the former, we use data from the Map the Meal Gap (MMG) project, which is broken down by Rural-Urban Continuum Codes. For the latter, we combine MMG data with data from the Hunger in America 2014 (HIA 2014) survey to determine the geographic distribution of charitable food assistance. At the national level, we find few differences across the rural-urban interface, but we do find differences within and across regions. We also find that regardless of how it is measured, the distribution of charitable food assistance is directed more toward counties with smaller populations—a finding that holds even after controlling for factors that influence the distribution of charitable assistance.